2020
DOI: 10.3390/molecules25225479
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble O-, S- and Se-Functionalized Cyclic Acetyl-triaza-phosphines. Synthesis, Characterization and Application in Catalytic Azide-alkyne Cycloaddition

Abstract: The 3,7-diacetyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane (DAPTA) derivatives, viz. the already reported 3,7-diacetyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane 5-oxide (DAPTA=O, 1), the novel 3,7-diacetyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane-5-sulfide (DAPTA=S, 2), and 3,7-diacetyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane-5-selenide (DAPTA=Se, 3), have been synthesized under mild conditions. They are soluble in water and most common organic solvents and have been characterized using 1H and 31P NMR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The coordination properties of the obtained phosphane molecules have been studied towards copper(I) to produce a novel set of hydrophilic Cu(I) complexes. In continuation of our contribution to the field of click chemistry by means of homogeneous [12,22,23,26,41] and carbon-supported catalysts [28], the three-component approach of the CuAAC reaction for microwave-assisted synthesis of 1,4-disubstituted-and 2-hydroxymethyl-1,2,3-triazoles in aqueous medium is tackled using the new Cu(I) complexes as catalysts in a homogenous system, and as heterogenized catalysts supported on activated carbon (AC) and multi-walled carbon nanotubes (CNT), thus aiming also a comparison between both catalysis methods and these types of carbon supports.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…The coordination properties of the obtained phosphane molecules have been studied towards copper(I) to produce a novel set of hydrophilic Cu(I) complexes. In continuation of our contribution to the field of click chemistry by means of homogeneous [12,22,23,26,41] and carbon-supported catalysts [28], the three-component approach of the CuAAC reaction for microwave-assisted synthesis of 1,4-disubstituted-and 2-hydroxymethyl-1,2,3-triazoles in aqueous medium is tackled using the new Cu(I) complexes as catalysts in a homogenous system, and as heterogenized catalysts supported on activated carbon (AC) and multi-walled carbon nanotubes (CNT), thus aiming also a comparison between both catalysis methods and these types of carbon supports.…”
Section: Introductionmentioning
confidence: 96%
“…Due to the high importance of 1,2,3-triazoles as components in pharmacologically active compounds, organic and inorganic polymers and materials, CuAAC has had a marked influence in several chemical applications [7][8][9]. Several studies indicated the positive influence of certain ligands to improve the efficiency of CuAAC, which are able to stabilize the Cu(I) catalyst and prevent its oxidation and disproportionation during the catalytic cycle [10][11][12]. In this context, several well-defined copper complexes bearing phosphines [13], polydentate amines [14], iminophosphoranes [15,16], N-heterocyclic carbenes [17][18][19] tris(triazolyl) methanol [20,21], tris(pyrazolyl) methanes [22], and arylhydrazones [23] as ligands have been applied as catalysts for the CuAAC reaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of microwave heating, as compared to conventional methods, has been shown to dramatically reduce reaction times, increase product yields and enhance product purity by reducing unwanted side reactions [26][27][28][29]. In continuation of our efforts to develop efficient catalytic CuAAC systems [25,[30][31][32]] compounds 1-4 were heterogenized in carbon materials (AC and CNT) and utilized as heterogeneous catalysts for the microwave-assisted synthesis of triazoles. The catalytic potential of the supported species are compared with the previously studied homogeneous counterparts [25].…”
Section: Introductionmentioning
confidence: 99%